Combination of Agile Development and User Centered Design to Improve the Usability of a Beef-Cattle Farm Simulator - Arroqui, Mauricio (2016)
At the Faculty of Veterinary Science of the National University of Buenos Aires Center a Beef-Cattle Farm simulator called Simugan has been developed. Simugan allows users to experiment over a virtual farm in a simple and low cost way compared with real farm conditions. Increased number of user led to the identification of deficits in Simugan usability, as inconsistency problems with inputs and outputs were difficult to understand by novel users. Therefore, a combination of agile development and user centered design (ADUCD) was applied to fix those identified problems. The results shown a high level of achievement with ADUCD (94% of methodology required criteria) as reported in user interviews and evaluation tests.